Golden hour eaudiobook - Battles, Brett (Teddy Fay, 2024)
Former CIA operative Teddy Fay returns for another heart-pounding Hollywood-fueled adventure in this latest installment in the New York Times bestselling series. Teddy Fay is ready to embark on the European press tour of Peter Barrington’s latest film Storm’s Eye , when he receives an unexpected visit from Lance Cabot, director of the CIA. Several CIA agents have been turning up dead. The commonality? They were all part of a mission Teddy was involved in: Golden Hour. Lance wants Teddy to use his trip as a cover to investigate who is behind these killings. From Venice and Budapest to their last stop at a film festival in Berlin, Teddy must dodge excited fans, enamored women, and a few too many assassins who seem dead set on tracking down Golden Hour agents. And if Teddy doesn’t work fast enough, his identity—and life—might just be the next target in the killer’s ruthless plot for revenge.